Resale of treasury shares: Malaysia evidence - Abdul Latif, Rohaida (2014)
The first objective of the study examines the announcement effects on resale of treasury shares among public listed firms in Malaysia. All firms that resale their treasury shares between 2001 and 2012 are examined using standard event methodologies namely market adjusted return (MAR) and market model (MM).The finding reveals that resale firms experience significant positive 4% abnormal returns in 5 days prior to the actual resale of treasury shares. There is no abnormal gains realize following the actual resale of treasury shares date suggesting that market is semi-strongly efficient where prices can fully reflect all publicly available information.The second objective is to assess the relationships between three companies' financial characteristics and the magnitude of shares resale, which is the percentage of shares resale in the open market (PRESALE).Based on signaling theory, it is found that both prior returns and current EPS are positively and significantly affecting the percentage of treasury shares resold in the market while LAGEPS has a negative and significant relationship with PRESALE.